STUDI PENGGUNAAN ASBUTON BUTIR PADA CAMPURAN BETON ASPAL BINDER COURSE (AC-BC) - Setiawan, Arief; Rahman, Rahmatang (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2011)
The use of natural asphalt (asbuton) in road pavement construction has been widely researched anddeveloped. One of them is a mixture of petroleum asphalt with asbuton. The purpose of this study wasto determine how the effect of granular Asbuton on a mixture AC-BC (Asphalt Concrete-BinderCourse).Type of Granular Asbuton used is Asbuton Type 15/25. The amount of Granular Asbuton used inasphalt mix are 7%, and 8% of total weight of the mixture. The number of test specimens in this studywere 117 specimens consisting of 54 to PKAO, 27 for the PRD, 24 for variation of the collision, 12 for theMarshall Immersion test and 6 to Optimum Asphalt Content.Based on the results of tests performed on a mixture of AC-BC with a modified bitumen 60/70 andgranular asbuton amount of 7% found that the Optimum Asphalt Content is 5.2%, Density values is2.378 gr/cm3 , VIM value is 4.871%, VMA value is 15.456%, the VFB value is 68.485%, the Marshall Stabilityvalue is1333.571 kg, the Marshall Quetion value is 333 690 kg/mm and Marshall Immersion Value is82.08%. Asphalt Concrete-Binder Course Mixture with the addition granular asbuton amount of 8%found that the Optimum Asphalt Content is 6,2%, Density values is 2,322 gr/cm3, VIM value is 5,01%,VMA value is 17,443%, VFB value is 71,303%, Marshall Stability value is 1563,27 kg, Marshall Questionvalue is 386.95 kg/mm and Marshall Immersion value is 82,45%.Based on the percentage of granular asbuton in Asphalt Concrete-Binder Course Mixture shows thatthe 8% of granular asbuton can be increased Marshall Stability and Marshall Immersion and OptimumAsphalt Content values.